Study of index of Relationship between Land Use Chang and Urban Heat Island of Mice City Pattaya - ปรีเปรมโมทย์ กมลวรรณ; ชวนะเวสสกุล สุธาทิพย์; ปิยะทัศนานนท์ พันทิพย์ (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
This study aims to study the correlation between land use and heat phenomena in Mice city Pattaya by the application of LANDSAT 5 TM satellite images from 27 January 2007,and 12 January 2012 and LANDSAT 8 OLI satellite images from 8 February 2016 to classify land use or level two land use or land use or land cover to analyze surface temperature by determining the relationship change index in terms of land use or land use or land cover by NDVI (Normalized Difference Vegetation Index), NDBI (Normalized Difference Built Index) and the NDWI (Normalized Difference Water Index) method. This study revealed that from 2007 to 2016, the land use or land use or land cover, such as city, commercial and services, village, roads, industrial land, perennial, and reservoir built-up have increased by about 5.0 Km2, 1.12 Km2, 0.06 Km2, 0.43 Km2, 0.05 Km2, 0.04 Km2, and 1.20 Km2. In contrast, institution, field crop, orchard, deciduous forest, natural water bodies, grass and scrub, wetland, and others have decreased by about 0.01 Km2, 1.25 Km2, 1.44 Km2, 0.01 Km2, 0.02 Km2, 2.55 Km2, and 0.21 Km2. The surface temperature changes related to land use or land use or land cover, such as city, commercial and services, village, institution, roads, industrial land, field crop, perennial, orchard, deciduous forest, natural water bodies, reservoir built-up, grass and scrub, wetland and others have increased by 12.7˚C, 12.7˚C, 13˚C, 12.3˚C, 13˚C, 13˚C, 14.6˚C, 13.6˚C, 11.5˚C, 11.7˚C, 13.0˚C, 13.5˚C and 12.7˚C. The change in the variance index over the last 10 years (2007-2016) identified a pattern of land use or land use or land cover have changed according to the economy of Mice city, Pattaya which met the overall demands of both businesspeople and tourists. The study of the relationship change index of land use or land use or land use or land cover with the surface temperature changes showing that NDVI was an inverse variation with the surface temperature. On the other hand, NDBI and NDWI were a direct variation regard to the surface temperature.